Transformation of Islamic Religious Education in the Revolution 4.0 Era - Musytari Randa; Muhammad Arsyam (GoAcademica Research & Publishing, 2022)
Technological developments demand adjustments in various fields, including the field of education. In order to meet the educational needs of the millennial generation, it is necessary to modernize Islamic Religious Education based on character education. This study aims to see how the future challenges of Islamic Religious Education and solutions so that Islamic Religious Education can survive in Indonesia. This research is a qualitative research. This research method is a literature study with data obtained from research results and previous studies that are still relevant to the research content. The results of this study then found a need for transformation in Islamic religious education to face future challenges. This transformation is in the form of changes in the face and curriculum of Islamic Religious Education. The forms of this transformation include the improvement of the applicable regulations; Future-oriented education; Curriculum review and improvement; Madrasa Management Quality Improvement; Increasing Madrasah Leadership Capacity and Capability; Teacher Competency Improvement; Community involvement in developing Madrasas; Digitalization of academic, administrative, and learning services.